Sintering behavior and dielectric properties of A3(PO4)2 compounds (A = Ca, Sr, Ba, Mg, Zn, Ni, Cu) - Cho, In Sun (Materials Science in Semiconductor Processing, 2022)
A series of divalent metal orthophosphate compounds, A3(PO4)2 (A = Ca, Sr, Ba, Mg, Zn, Ni, Cu), were synthesized using a solid-state reaction method. The densification behavior and optical properties of the synthesized powders were investigated using differential thermal analysis, dilatometry, and UV–Vis diffuse reflectance spectroscopy. The crystal structure and microstructure of the sintered samples were investigated using X-ray powder diffractometry and field-emission electron microscopy. We found that orthophosphate ceramics could be sintered at comparatively low temperatures ranging from 900 to 1225 °C. In particular, Ca3(PO4)2, Mg3(PO4)2, and Zn3(PO4)2 exhibited volume expansion during the sintering process due to the phase transformation, which impedes further densification by microcrack formation. The dielectric properties were measured in the microwave frequency region by using a network analyzer. The results revealed that the orthophosphate ceramics exhibited low dielectric constants (5.4–12.5) and high-quality factor values ranging from 10,300 to 62,000 GHz. More importantly, the temperature coefficients of the resonant frequency values of Ba3(PO4)2 and Sr3(PO4)2 were positive, and the others were negative. Differences in microwave dielectric properties are discussed in terms of chemical bonding, such as bond strength and bond valence.
Keywords: Behaviour properties; Bond covalence; Dielectrics property; Divalent metals; Optical-; Orthophosphate; Sintering behaviors; Solid state reaction method; Synthesised; Thermal; Bond covalence; Dielectric properties; Optical; Orthophosphates; Sintering; Thermal